DINAMIKA PERKEMBANGAN PETANI KOPI BINAAN KPSU SOLOK RADJO DALAM PRAKTIK TECHNOSOCIOPRENEURSHIP - Yonaldi, Sepris; Noer, Melinda; Hendri Yeni, Yulia; Nofialdi (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
The aim of this research is to examine the dynamics of development of coffee farmers assisted by KPSU Solok Radjo in the practice of technosociopreneurship. The research method approach is a qualitative method. Qualitative data was used to explore the views of cooperative managers and members, as well as coffee farmers assisted by the Solok Radjo KPSU Cooperative. Semi-structured interviews were conducted with several key informants, namely coffee farmers as development partners, cooperative members and KPSU Solok Radjo managers. The findings of this research; 1) The Solok Radjo KPSU Cooperative plays a role in realizing SDGs goals in order to solve social problems of farming communities, for example reducing poverty, increasing income and keeping the environment green. 2) Bringing changes to the lives of coffee farmers by increasing coffee prices at the farmer level, because farmers' agricultural products are directly managed by cooperatives, both for export and for downstream retail products. 3) Increasing farmers' knowledge about coffee cultivation, one example is that farmers have picking standards which affect the quality of coffee beans. 4) Assisted farmers can use Dimitra technology as a digital-based transaction medium. 5) Coffee farmers have new business opportunities with the corporate farming program in waste processing, where this program will provide many solutions to the community's economic, environmental and social problems. The active involvement of farmers and cooperative members is a solid foundation on which KPSU Solok Radjo is built in developing capital assets and social capital. This is the driving force for business development with technological innovation for farmers.